PRESUPPOSITIONS IN MOBILE PHONE ADVERTISEMENTS (NOBEL: Journal of Literature and Language Teaching, 2015)
The present study aims to describe the types of presuppositions contained in mobile phone advertisement and to describe the functions of presuppositions contained in mobile phone advertisement. The descriptive will describe and interpret phenomena related to presuppositions. The analysis of the mobile phone advertisements shows that the most dominant type of presuppositions found in selected slogans is lexical presuppositions. In terms of the functions of presuppositions in the advertisement, committing in implicit competition and making the advertisement short and memorable is the functions which are most frequently used.